Atomic-level engineering of single Ag 1+ site distribution on titanium–oxo cluster surfaces to boost CO 2 electroreduction - Meng, Ru-Xin; Zhao, Lan-Cheng; Luo, Li-Pan; Tian, Yi-Qi; Shao, Yong-Liang; Tang, Qing; Wang, Likai; Yan, Jun; Liu, Chao (Chemical science (Cambridge), 2025)
Precise control over the distribution of active metal sites on catalyst surfaces is essential for maximizing catalytic efficiency. Addressing the limitations of traditional cluster catalysts with core-embedded catalytic sites, this work presents a strategy to position catalytic sites on the surfaces of oxide clusters. We utilize a calixarene-stabilized titanium–oxo cluster (Ti12L6) as a scaffold to anchor Ag 1+ in situ , forming the unique nanocluster Ti12Ag4.5 with six surface-exposed Ag 1+ sites. The in situ transformation from Ti12L6 into Ti12Ag4.5 clusters was traced through mass spectrometry, revealing a solvent-mediated dynamic process of disintegration and reassembly of the Ti 12 L 6 macrocycle. The unique Ti12Ag4.5 cluster, featuring a surface-exposed catalytic site configuration, efficiently catalyzes the electroreduction of CO 2 to CO over a broad potential window, achieving CO faradaic efficiencies exceeding 82.0% between −0.4 V and −1.8 V. Its catalytic performance surpasses that of bimetallic Ti2Ag2, which features a more conventional design with Ag 1+ sites embedded within the cluster. Theoretical calculations indicate that the synergy between the titanium–oxo support and the single Ag 1+ sites lowers the activation energy, facilitating the formation of the *COOH intermediate. This work reveals that engineered interactions between active surface metal and the oxide support could amplify catalytic activity, potentially defining a new paradigm in catalyst design.